Canadian Television Today - Sullivan, Rebecca; Beaty, Bart (Op/positions, 2006)
What's on TV? Canadian Television Today explores the current challenges and issues facing the English-language television industry in Canada. Television in Canada has long been one of the principal conduits of national identity. But has it kept pace with the rapidly changing landscape of Canadian culture? After presenting an overview of the main issues and debates surrounding the Canadian small screen, Beaty and Sullivan offer their suggestions for the future of the medium. They argue that in today's globalized world, Canadian television should be a more fitting reflection of Canada's multicultural society, embracing a broader range of languages, cultures, and viewing strategies. Visualizing the potential reach of a revitalized industry, Beaty and Sullivan illustrate the promise and possibility of Canadian television that serves the cultural needs of all its citizens.